ANALYSIS OF FACTORS CAUSING MISCONCEPTIONS IN GUIDANCE AND COUNSELING - Gusman Lesmana; Rafida Annisa; Tashya Natiyu Tirana (Faculty of Tarbiyah nad Teacher Training, 2023)
Misconceptions are incorrect explanations of ideas that are not in accordance with the scientific understanding accepted by experts. Misconceptions often occur because the concepts studied and accepted are different. The aim of this research is to find out what misconceptions there are regarding guidance and counseling services. The technique used in writing this article is a bibliographic display method that uses literature such as journals, books, documents and other sources without conducting field research. This article contains an abstract, introduction, discussion and conclusion.